EFFECT OF WORK DISCIPLINE AND ENVIRONMENT WORK AND MOTIVATION OF EMPLOYEES PERFORMANCE SUB-DISTRICT AT DISTRICT MUSI BANYUASIN - Deri Apriliyani; Fatimah Fatimah; Omar Hendro (STIE DWI SAKTI BATURAJA, 2020)
This study aims to determine the effect of work discipline and work environment and work motivation both together and partially on the performance of employees at the Musi Banyuasin District Office. The data used in this study are secondary data and primary data from the answers of 111 respondents. The analytical model used is multiple linear regression analysis and through testing of validity and reliability instruments. Data tests are normality test and linearity test and multicollinearity test model and heteroscedasticity test. The results of the F-Test show that there is a positive and significant influence of discipline, environment and work motivation together on employee performance. The results of the T-test show that there is a positive and significant influence on discipline, environment and work motivation partially on employee performance. Increasing and decreasing discipline, work environment and work motivation influence employee performance.